Biogenesis and function of non-coding RNAs in muscle differentiation and in Duchenne muscular dystrophy. (18th July 2013) - Twayana, Shyam; Legnini, Ivano; Cesana, Marcella; Cacchiarelli, Davide; Morlando, Mariangela; Bozzoni, Irene
Abstract : It is now becoming largely accepted that the non-coding portion of the genome, rather than its coding counterpart, is likely to account for the greater complexity of higher eukaryotes. Moreover, non-coding RNAs have been demonstrated to participate in regulatory circuitries that are crucial for development and differentiation. Whereas the biogenesis and function of small non-coding RNAs, particularly miRNAs (microRNAs), has been extensively clarified in many eukaryotic systems, very little is known about the long non-coding counterpart of the transcriptome. In the present review, we revise the current knowledge of how small non-coding RNAs and lncRNAs (long non-coding RNAs) impinge on circuitries controlling proper muscle differentiation and homoeostasis and how their biogenesis is regulated. Moreover, we provide new insights into an additional mechanism of post-transcriptional regulation mediated by lncRNAs, which, acting as miRNA 'sponges', have an impact on the distribution of miRNA molecules on their targets with features similar to those described for ceRNAs (competing endogenous RNAs).